Study the Readiness of Souphanuvong University to be Independent in Budget Management by Mathematic Model - Saybounheaung, Thongsouk; Lilianou, Lisatteur; Souksomvang, Phoui; Vongbounsy, Parnthong; Bounphanmy, Somchan (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study is to study the readiness factors of Souphanuvong University to be independent in budget management, which focus on three objectives: 1) To study the sequence of readiness factors that affect the Souphanuvong University to be independent in budget management; 2) To study the level of readiness factors that affect the Souphanuvong University to be independent in budget management;; 3) To collect comments, requests and suggestions of the questionnaire respondents towards the Souphanouvong University to improve itself to the high level based on the factors studied. The sample group was 129 people including teachers and admistrative officers who has got the position of deputy-head of division to to President of the university. The study tools used five-level assessment questionnaires and data analysis. There are two methods: statistical method, Analytic Hierarchy Process (AHP) and Fuzzy Modeling. The results of this study showed that: From the sequence analysis of key readiness factors of Souphanuvong University to be independent in budget management on each side (P, A, M, I, O, C) can prioritize from the most important factors to the least one; the order is: for 1st factor, the factor of Management (M); the 2nd one, the Income (I); the 3rd one, the Personnel (P); the 4th one, the Outcome (O); the 5th one, the Academic (A); and the last one, the Control of Income and Expense. For level of readiness factors of Souphanuvong University to be independent in budget management will be shown as the following: the Academic (A) factor is at high level of readiness; the Outcome (O) factor is at high prepareness; the Management (M) factor is at high level; the factor of Control (C) of income and expense is high level too; the Personnel (P) factor is at high; and the factor of Income is also high readiness. Overall, the level of readiness factors of Souphanuvong University to be independent in budget management in the five components is very high with a value of 3.4548. For the suggestion of the questionnaire respondents can be summarized as following: The income of the Souphanouvong University is only from the Lao government and registration fee. Therefore, it is better if the university can have the regulation to take tax from teachers who have extra projects or teach outside the university as a part time job.